2020
DOI: 10.1099/mgen.0.000362
|View full text |Cite
|
Sign up to set email alerts
|

Identification of genes required for the fitness of Streptococcus equi subsp. equi in whole equine blood and hydrogen peroxide

Abstract: The availability of next-generation sequencing techniques provides an unprecedented opportunity for the assignment of gene function. Streptococcus equi subspecies equi is the causative agent of strangles in horses, one of the most prevalent and important diseases of equids worldwide. However, the live attenuated vaccines that are utilize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 69 publications
0
5
0
Order By: Relevance
“…Streptococcus equi in horse blood or hydrogen peroxide 66 , the demonstration that oxidative stress resistance enhances V. cholerae host adaptation in a mouse model 67 , survival of Burkholderia cenocepacia in a Caenorhabditis elegans host 68 , Streptococcus mutans infection in an oral rodent model 69 and the building of a targeted sublibrary of type IV secreted proteins in the intracellular pathogen Coxiella burnetii using INSeq, which was subsequently screened for vacuole formation in human HeLa cells 70 .…”
Section: Reverse Geneticsmentioning
confidence: 99%
“…Streptococcus equi in horse blood or hydrogen peroxide 66 , the demonstration that oxidative stress resistance enhances V. cholerae host adaptation in a mouse model 67 , survival of Burkholderia cenocepacia in a Caenorhabditis elegans host 68 , Streptococcus mutans infection in an oral rodent model 69 and the building of a targeted sublibrary of type IV secreted proteins in the intracellular pathogen Coxiella burnetii using INSeq, which was subsequently screened for vacuole formation in human HeLa cells 70 .…”
Section: Reverse Geneticsmentioning
confidence: 99%
“…1C). TraDIS was used to identify genes with a significantly altered mutant frequency in the output mutant pools relative to the input pools, as described previously (62)(63)(64). Genes with a significantly decreased mutant frequency (log 2 fold change of Ͼ1, q value of Ͻ0.1) in the output mutant pools were regarded as important for growth and persistence in whole blood (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Processing of TraDIS sequencing reads and data analysis. Processing of TraDIS sequencing reads and data analysis were performed as previously described (62)(63)(64). Sequencing reads were analyzed with the TraDIS toolkit (24).…”
Section: Methodsmentioning
confidence: 99%
“…These screens have been widely used to discover new factors involved in bacteremia of the most clinically relevant bacteria such as S. aureus (Mei et al 1997 , Coulter et al 1998 , Benton et al 2004 , Christiansen et al 2014 , Valentino et al 2014 , Oogai et al 2016 , Groma et al 2020 ) or E. coli (Phan et al 2013 , Subashchandrabose et al 2013 , McCarthy et al 2018 , Ma et al 2021 ) as well as other bacteria associated with bloodstream infection such as A. baumannii (Subashchandrabose et al 2016 , Sanchez-Larrayoz et al 2017 ), Citrobacter freundii (Anderson et al 2018 ), E. faecium (Zhang et al 2017 ), H. influenzae (Langereis and Weiser 2014 ), K. pneumoniae (Short et al 2020 , Holmes et al 2022 ), Leptospira interrogans (Lourdault et al 2016 ), N. meningitidis (Sun et al 2000 , Geoffroy et al 2003 , Mendum et al 2011 , Capel et al 2017 ), Pasteurella multocida (Fuller et al 2000 ), Proteus mirabilis (Armbruster et al 2019 ), P. aeruginosa (Janet-Maitre et al 2023 ), S. enterica (Hensel et al 1995 , Chaudhuri et al 2009 ), S. marcescens (Anderson et al 2017 ), S. agalactiae (Hooven et al 2018 , Zhu et al 2020 , Dammann et al 2021 ) , Streptococcus equi (Charbonneau et al 2020 ), S. pneumoniae (Polissi et al 1998 , Mann et al 2012 ), S. pyogenes (Le Breton et al 2013 , van Hensbergen et al 2018 ), S. suis (Arenas et al 2020 ), Y. pestis (Palace et al 2014 ) or Y. pseudotuberculosis (Crimmins et al 2012 ). Additionally, a genetic screen using a library of K. pneumoniae transposon mutant recently iden...…”
Section: Bacterial Metabolic Factorsmentioning
confidence: 99%
“…Using random transposon mutagenesis coupled with sequencing, de novo biosynthesis genes previously reported in nonpathogenic E. coli (Samant et al 2008 ) were identified in ExPEC grown in swine serum, and loss of virulence of PurF and PyrF mutants was confirmed in a mouse model of infection (Ma et al 2021 ). New screens mostly based on transposon mutagenesis (see Box 2 and Supplementary Table S11 ) further highlighted requirement of nucleotide biosynthetic pathways for bacterial survival in blood or in vivo for other bacteria such as in several Streptococcus species (Polissi et al 1998 , Le Breton et al 2013 , Hooven et al 2018 , Charbonneau et al 2020 , Zhu et al 2020 , 2021 ), Y. pseudotuberculosis (Crimmins et al 2012 ), Y. pestis (Palace et al 2014 ), N. meningitidis (Sun et al 2000 , Mendum et al 2011 , Capel et al 2017 ), P. multocida (Fuller et al 2000 ), P. mirabilis (Armbruster et al 2019 ), S. aureus (Benton et al 2004 , Christiansen et al 2014 , Connolly et al 2017 , Groma et al 2020 ), K. pneumoniae (Weber et al 2020 ) or E. faecium (Zhang et al 2017 ). By combining Tn-Seq with RNA-Seq this latter study pointed out upregulation of expression of the purine biosynthesis operon during bacterial growth in serum.…”
Section: Bacterial Metabolic Factorsmentioning
confidence: 99%